Analysis of Flavonoids by b-Cyclodextrin Modified Capillary Zone Electrophoresis in Traiditional Chinese Medicine - Ning, Z.; Zhong, H.; Kong, C.; Lu, Y. (Asian Journal of Chemistry, 2012)
A b-cyclodextrin modified capillary zone electrophoresis method was developed to determine flavonoids in traiditional Chinese medicines. After optimization, the optimum separation conditions were selected as: a background electrolyte of 20 mmol L-1 Borax (pH 7.5) containing 6 mmol L-1 b-cyclodextrin and 20 % (v/v) acetonitrile and injection time of 65 s. Under these conditions the sensitivity was enhanced 15 to 17 times when compared to a normal hydrodynamic injection. Detection limits for the five flavonoids acids were in the range of 15-30 ng mL-1. The developed method was further verified by application to traditional Chinese medicine real sample analysis with good results.